Analisis Strategi Pengembangan Bisnis PT. TAF (Toyota Astra Financial Services) - Ari Surya Rusdiono; Alla Asmara; Kirbrandoko Kirbrandoko (IPB University, 2019)
PT.TAF is one of financial company in Indonesia. The business model that has been implemented so far is highly dependent on dealer as business partner. In 2017 and 2018, the company suffered quite a lot of losses that caused of high Non Performing Loan (NPL). This is caused by decrease in existing consumer’s segment so the profit of company decrease more than 80 percent. There were management and organization structure changes in 2018, which lead to the expectation of company’s performance improvement. Therefore, new strategy is needed to enhance company’s performance. Interviews were conducted with interviewess (Director, General Manager, Department Head) selected by purposive sampling to identify company’s internal and external strategic issues. The Internal Factor Evaluation matrix (IFE) and External Factor Evaluation matrix (EFE) are used to evaluate company’s internal and external conditions. Strength, Weaknesses, Opportunities, and Threat (SWOT) matrix is used to find alternative strategies to improve company performance. And then the alternative strategies are selected to find the priority using Quantitative Strategic Planning Matrix (QSPM). There are 6 alternative strategies to improve company performance and from those strategies, two strategies were choosen as main priority that will be executed by the company. The two strategies are create application (digitizing)information, simulations, credit applications for consumer and dealer also increase spred (profit margin) of consumers who will pay off or have paid off (good credit history) with non retail financing program.